Risk Management in Sharia Insurance - Khairul Azmi; Sugianto Sugianto; Marliyah Marliyah (Budapest International Research and Critics University, 2022)
Risk management is a benchmark for every institution and organization in minimizing the risks that occur. Where decisions taken must take into account Islamic law. All forms of risk that occur continue to prioritize the concept of sharia. This paper is descriptive qualitative, which explains about risk management, then risk management in sharia concepts, and risk management in insurance institutions. The results of this paper indicate that risk management has various processes, namely, identification, evaluation and measurement, and risk management. Insurance is one way to manage risk, it's just that until now there is still an assumption that insurance is against destiny. Sharia insurance as an endeavor, which is not contrary to the concept of trustworthiness. The form can be in the form of operational risk (operational risk) such as failure to pay, legal risk (legal risk), and reputation risk (reputation risk) in addition to moral hazard is also often encountered obstacles faced by the company is sourced from external and internal company. In managing risk, Islam provides a solution with the concept of risk sharing.